Stigmatizing attitudes, beliefs, and actions of women towards abortion in rural regions with high fertility - Akbulut, Sahide; Kılıçlı, Ayşegül (Modestum Ltd, 2022)
Objectives: The study aims to determine the stigmatizing attitudes, beliefs, and actions of women towards abortion in rural and conservative areas where fertility is high. Methods: The research is cross-sectional. It was carried out in Mus State Hospital between 28 March-28 April 2022. The sample of the study consisted of 499 women. Introductory information form and stigmatizing attitudes, beliefs, and actions scale towards abortion were used as data collection tools. Findings: The participants' mean score of stigmatizing attitudes, beliefs, and actions towards abortion scale 69.5, negative stereotypes 28.3, discrimination and exclusion 29.1, and fear of contagion sub-dimension 11.9. The mean score of the scale was found to be significantly higher in women who are single, between 20-35 ages, live in the city center and nuclear family, have an undergraduate or above education level, work (p<0.05). There was a negative correlation between the scale mean score of women and the number of pregnancies, births, living children; and a positive correlation between the scale mean score and the number of abortions (p<0.05). Conclusions: It was found out that stigmatizing and negative attitudes, beliefs, and actions towards abortion are high among women in rural regions with high fertility.
Keywords: abortion; stigma; attitude; belief; action; Disclosure; Scale